Network meta-analysis of intravitreal conbercept as an adjuvant to vitrectomy for proliferative diabetic retinopathy - Wang, Weiwei; Qu, Chaoyi; Yan, Huanhuan (Frontiers in Endocrinology, 2023)
Purpose: Intravitreal Conbercept (IVC) has been shown to be effective in treating proliferative diabetic retinopathy (PDR) as an adjuvant in pars plana vitrectomy (PPV); however, the best timing of IVC injection remains unknown. This network meta-analysis (NMA) sought to ascertain the comparative efficacy of different timings of IVC injection as an adjuvant to PPV on PDR. Methods: A comprehensive literature search was conducted in PubMed, EMBASE, and the Cochrane Library to identify relevant studies published before August 11, 2022. According to the mean time of IVC injection before PPV, the strategy was defined as very long interval if it was > 7 days but ≤ 9 days, long interval if it was > 5 days but ≤ 7 days, mid interval if it was > 3 days but ≤ 5 days, and short interval if it was ≤ 3 days, respectively. The strategy was defined as perioperative IVC if IVC was injected both before and at the end of PPV, and the strategy was intraoperative IVC if injected immediately at the end of PPV. The mean difference (MD) and odds ratio (OR) with corresponding 95% confidence interval (CI) for continuous and binary variables, respectively, were computed through network meta-analysis using Stata 14.0 MP. Results: Eighteen studies involving 1149 patients were included. There was no statistical difference between intraoperative IVC and control in treating PDR. Except for a very long interval, preoperative IVC significantly shortened operation time, and reduced intraoperative bleeding and iatrogenic retinal breaks. Long and short intervals reduced endodiathermy application, and mid and short intervals reduced postoperative vitreous hemorrhage. Moreover, long and mid intervals improved BCVA and central macular thickness. However, very long interval was associated with an increased risk of postoperative vitreous hemorrhage (RR: 3.27, 95%CI: 1.84 to 5.83). Moreover, mid interval was better than intraoperative IVC in shortening operation time (MD: -19.74, 95%CI: -33.31 to -6.17). Conclusions: There are no discernible effects of intraoperative IVC on PDR, but preoperative IVC, except for very long interval, is an effective adjuvant to PPV for treating PDR.